Transação em matéria tributária: fundamentos para uma regulamentação em âmbito federal - Mickelberg, Michelle Camini (2018)
The research investigates whether the application of the transaction in tax law, understood as one of the possible outcomes of the consensual methods of dispute resolution, is compatible with the Brazilian judicial system and, in case it is, what are the limits imposed by the legal system to its federal regulation. This work starts with the assumption that language is constitutive of reality and seeks to identify what are the possible meanings of the word transaction; starting from the characteristics of the out-of-court methods of dispute resolution and the civil transaction, as well as from the analysis of the rule described in article 171 of the National Tax Code (CTN), a definition of the tax transaction concept is built. In face of the definition of this institute, this work studies the elements of the rule to be introduced by the Federal Legislative Power, as well as its compatibility with article 3rd of the CTN, with the constitutional norms that rule the national tax system and with the public interest. This work also analyzes the possibility of a legal claim on the transaction and the legal consequences resulting from possible flaws in the agreement between the State and the individual. Closing the research, this work investigates the cost-benefit in the insertion of a federal law regulating the tax transaction, taking into consideration the incentives generated on taxpayers for such legislative choice, the economic benefits reaped by the Fiscal Authority in the adoption of this institute and whether the perspective of an agreement with the State could increase tax evasion and corruption. Finally, the previous experiences of tax transaction in states and local legislations is analyzed considering the resulting conclusions of the present study